2004
DOI: 10.1103/physreve.70.041705
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of orientational order parameters of a ferroelectric liquid crystal

Abstract: A method of determining the set of four order parameters S , D , P , and C for a ferroelectric liquid crystal, using complementary results for different sample geometries, is presented. IR measurements have been performed for homeotropic, planar heterogeneous and, planar homogenous sample geometries. Orientational order parameters were determined in two frames of reference to obtain complete information on molecular arrangement. Results for the D , P , and C parameters indicate the importance of both the intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The equilibrium probability p n is then obtained using Eq. (66). While S is used in calculating the proton T 1 , both S and p n are needed for calculating the spectral densities for each deuteron site.…”
Section: Calamitic and Chromonic Mesogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium probability p n is then obtained using Eq. (66). While S is used in calculating the proton T 1 , both S and p n are needed for calculating the spectral densities for each deuteron site.…”
Section: Calamitic and Chromonic Mesogensmentioning
confidence: 99%
“…prefers to align either more toward X or Y axis. It has been shown both theoretically [64] and experimentally [6,65,66] that P is usually small in a SmC phase.…”
Section: Introduction To Liquid Crystalsmentioning
confidence: 98%
“…For nematic liquid crystals, the ODF is described in terms of the generalised Legendre polynomials and order parameters where the indices , and take integer values. There are many approaches to measuring the order parameter in liquid crystals including electron spin resonance spectroscopy [1,2], x-ray [3,4,5,6,7,8], optical techniques [9], neutron scattering [10,11], and analysis of infrared spectra [12,13,14] . However, polarized Raman spectroscopy (PRS) is an important optical technique since it can be used to obtain not only the second order term , but also the next higher order term with L = 4, a parameter that can be obtained by very few other experimental methods [3,15,16,17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Most experiments have been performed for planar sample configuration; however, in the early 2000s, the alternative way of studying the most important order parameters and the molecular tilt angle was proposed. 22,23 Finally, vibrational spectroscopy has become a relevant tool in the studies of de Vries type 24 or biaxial nematic phases. 25−27 As modern quantum chemistry allows us to predict the vibrational spectra with very good accuracy, the experimental data may be nowadays deeply understood and interpreted, giving even further information about the components of the related transition moments, despite the high complexity of the recorded data.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the early works by Kocot et al dealing with order parameters and molecular tilt angle, many papers presenting successful application of infrared spectroscopy were reported. In parallel, significant papers by Kim et al have confirmed the applicability of Raman spectroscopy in related studies and opened the discussion for antiferroelectric liquid crystals. Most experiments have been performed for planar sample configuration; however, in the early 2000s, the alternative way of studying the most important order parameters and the molecular tilt angle was proposed. , Finally, vibrational spectroscopy has become a relevant tool in the studies of de Vries type or biaxial nematic phases. As modern quantum chemistry allows us to predict the vibrational spectra with very good accuracy, the experimental data may be nowadays deeply understood and interpreted, giving even further information about the components of the related transition moments, despite the high complexity of the recorded data. …”
Section: Introductionmentioning
confidence: 99%